KEBIJAKAN PERTANGGUNGJAWABAN PIDANA OLEH PELAKU KEJAHATAN TERHADAP HARTA BENDA ( STUDI KASUS TERHADAP RECIDIVIS ) - Dian Puspita Evariani, Eko Soponyono, Sularto (Diponegoro Law Journal, 2013)
Law enforcement is a legal certainty that promotes excessive legisme view, a constraint entry legal principles and values (justice) who want to uphold the law in court. Law enforcement to ignore the value of justice can affect the image of the legal and law enforcement in the public eye. Policies regarding the criminal responsibility  of  judges  in  decisions  on  PN  Semarang   what  recidivis  in accordance with the rules of the Penal Code governing recidive or even  seen  a case  with  more  discretion.  The  problem  is   how  the  policy  of   criminal responsibility by judge recidivis in the present and how the settings in the future. This thesis first discusses the policies of criminal responsibility by perpetrators of crimes against property  especially recidivis theft relating to the setting of the Criminal Code. Second, the concept of  repetition in settings offender Criminal Code of 2012.